Celebrity Support and Service Quality on Customer Satisfaction Mediated by Brand Image of Tokopedia Users - Lastyawati, Trizki; Harsono, Soni; Abdillah, Ulil Absor Faiq (Jurnal Manajemen Bisnis, 2024)
Tokopedia, currently ranked second, trails behind Shopee, indicating the need for enhanced performance to secure the top spot. This study delves into understanding consumer behavior and the factors shaping customer satisfaction in the e-commerce landscape, with a specific focus on Tokopedia. With Indonesia witnessing a surge in e-commerce activity amidst technological advancements and fierce market competition, the research explores the impact of celebrity endorsements, service quality, and brand image on customer satisfaction. Through quantitative analysis, involving 160 participants, the study reveals that celebrity endorsements and service quality significantly influence brand image positively. However, while celebrity endorsements and service quality do not directly impact customer satisfaction, brand image emerges as a key mediator, positively affecting customer satisfaction. Thus, the findings underscore the pivotal role of brand image in shaping customer perceptions and satisfaction levels, indicating avenues for Tokopedia to enhance its performance and competitiveness in the e-commerce landscape.